Market segmentation by psychographic criterio : an essay on the main psychographic theoretical approaches and its relationship with performance criteria - Ciribeli, João Paulo (2014)
Fil: Ciribeli, João Paulo. Universidad Nacional de Misiones. Facultad de Ciencias Económicas; Argentina.